Effect of Solvent Polarity on Antioxidant and Antidiabetic Activity of Kesambi Leaf Extract (Schleichera oleosa L.) - Nursamsiar Nursamsiar; Marwati Marwati; Fitriyanti J. Sami; Syamsu Nur; Henny Kasmawati; Aiyi Asnawi (Postgraduate, University of Mataram, 2025)
Kesambi (Schleichera Oleosa (L.) is one of the beneficial plants in Indonesia which contains fenolic and flavonoids that exhibit antioxidant properties. The presence of antioxidants in plants could be associated with antidiabetic activity of these plants. This research was conducted to determine the antioxidant and antidiabetic activities of n-hexane, ethyl acetate, acetone and methanol extracts from Kesambi leaves. Extraction was carried out by the ultrasonic assisted extraction (UAE) method. The antioxidant activity was determined quantitatively by DPPH and ABTS method, while the antidiabetic activity was evaluated by using α-glukosidase inhibition method. The IC50 values from the determination of antioxidant and antidiabetic activities were obtained by using Microplate reader at the maximum wavelength. Results of the antioxidant determination DPPH method showed that IC50 values of n-hexane, ethyl acetate, acetone and methanol extracts were 414.1993; 57.7862; 6.33 dan 13.4558 µg/mL, respectively. And for ABTS method showed 162.679; 22.6684; 10.7975; dan 146.869 µg/mL. This indicates the acetone and methanol extracts give the best results in antioxidant activity. Meanwhile, IC50 values of in vitro antidiabetic activity of n-hexane, ethyl acetate, acetone and methanol extracts were 99.3235; 272.8723; 1.6799; dan 24.4653 µg/mL, respectively. Acetone and methanol extracts of kesambi leaf give the best results in antidiabetic activity.